Trace residue identification, characterization, and longitudinal monitoring of the novel synthetic opioid β‐U10, from discarded drug paraphernalia. Issue 9 (23rd May 2022) - West, Henry; Fitzgerald, John L.; Hopkins, Katherine L.; Leeming, Michael G.; DiRago, Matthew; Gerostamoulos, Dimitri; Clark, Nicolas; Dietze, Paul; White, Jonathan M.; Ziogas, James; Reid, Gavin E.
Abstract: Empirical data regarding dynamic alterations in illicit drug supply markets in response to the COVID‐19 pandemic, including the potential for introduction of novel drug substances and/or increased poly‐drug combination use at the "street" level, that is, directly proximal to the point of consumption, are currently lacking. Here, a high‐throughput strategy employing ambient ionization‐mass spectrometry is described for the trace residue identification, characterization, and longitudinal monitoring of illicit drug substances found within >6, 600 discarded drug paraphernalia (DDP) samples collected during a pilot study of an early warning system for illicit drug use in Melbourne, Australia from August 2020 to February 2021, while significant COVID‐19 lockdown conditions were imposed. The utility of this approach is demonstrated for the de novo identification and structural characterization of β‐U10, a previously unreported naphthamide analog within the "U‐series" of synthetic opioid drugs, including differentiation from its α‐U10 isomer without need for sample preparation or chromatographic separation prior to analysis. Notably, β‐U10 was observed with 23 other drug substances, most commonly in temporally distinct clusters with heroin, etizolam, and diphenhydramine, and in a total of 182 different poly‐drug combinations. Longitudinal monitoring of the number and weekly "average signal intensity" (ASI) values of identified substances, developed here as a semi‐quantitative proxy indicator of changes in availability, relative purity and compositions of street level drug samples, revealed that increases in the number of identifications and ASI for β‐U10 and etizolam coincided with a 50% decrease in the number of positive detections and an order of magnitude decrease in the ASI for heroin. Abstract : A high‐throughput strategy employing ambient ionization‐mass spectrometry analysis of >6, 600 discarded drug paraphernalia (DDP) samples is described for the trace residue identification and longitudinal monitoring of dynamic alterations in illicit drug supply markets in response to the COVID‐19 pandemic, including for de novo identification and characterization of β‐U10, a previously unreported naphthamide analogue within the 'U‐series' of synthetic opioid drugs. Notably, β‐U10 was observed with 23 other drug substances and in a total of 182 poly‐drug combinations.